ANTIPLASMODIAL ACTIVITY OF KETOTIFEN-ARTEMETHER-LUMEFANTRINE ON PLASMODIUM BERGHEI INFECTED MICE - Georgewill, Udeme O.; Ezeriohaa, Chidi E.; Adikwu, Elias (International Journal of Research -GRANTHAALAYAH, 2020)
Introduction: The development of new antimalarial drugs is time-consuming and costly, thus repurposing of drugs with initial indications for possible antimalarial indication is imperative. This study assessed the antiplasmodial effect of ketotifen (KT) in combination with artemether/lumefantrine (A/L) in Plasmodium bergei infected mice. Materials and Methods: Adult mice (25-30g) were parasitized with Plasmodium berghei, grouped and treated per oral (p.o) with KT (0.1mg/kg), A/L (2.3/13.7mg/kg) and KT/A/L daily in curative, suppressive and prophylactic studies. The negative control (NC) and the positive control (PC) were treated daily p.o with normal saline (0.2mL) and chloroquine (CQ) (10mg/kg) for 4 days respectively. After treatment, blood samples were collected and assessed for percentage parasitemia level, hematological and lipid parameters. Results: The curative, suppressive and prophylactic studies showed significant decreases in percentage parasitemia levels at KT (0.1mg/kg) (p<0.01), A/L (2.3/13.7 mg/kg) (p<0.001) and KT/A/L (p<0.0001) when compared to negative control. Significant increases in mean survival times occurred at KT (0.1 mg/kg) (p<0.01), A/L (2.3/13.7mg/kg) (p<0.001) and A/L/T (p<0.0001) when compared to negative control. Significant increases in packed cell volume, red blood cells, hemoglobin, high density lipoprotein cholesterol levels with significant decreases in total cholesterol, white blood cells, low density lipoprotein cholesterol and triglyceride levels at KT (28.6 mg/kg) (p<0.05), A/L (2.3/13.7mg/kg) (p<0.01) and KT/A/L (p<0.001) when compared to negative control. Conclusion: KT may be repurposed in combination with A/L for malaria treatment.